2005
DOI: 10.1080/10556780500139690
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Lagrangian method for large-scale linear programming problems

Abstract: The augmented Lagrangian and Newton methods are used to simultaneously solve the primal and dual linear programming problems. The proposed approach is applied to the primal linear programming problem with a very large number (≈10 6 ) of nonnegative variables and a moderate (≈10 3 ) number of equality-type constraints. Computation results such as the solution of a linear programme with 10 million primal variables are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In each iteration of the modified L-shaped algorithm, master problem (26) or (27) and subproblems (8) are solved. Although, if the current point is feasible, N concave, piecewise quadratic, unconstrained maximization problems (28) have to be solved as well.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In each iteration of the modified L-shaped algorithm, master problem (26) or (27) and subproblems (8) are solved. Although, if the current point is feasible, N concave, piecewise quadratic, unconstrained maximization problems (28) have to be solved as well.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…(14) It can be shown that if β is sufficiently large, solving the inner maximization problem in (14) gives the unique solution of the problem (9). Therefore, instead of problem (14), we propose to solve the unconstrained maximization problem [8] max p∈R m 2 S(p, β,ŷ) (15) in which β,ŷ are constants and the function S(p, β,ŷ) is defined by…”
Section: Optimality Cutmentioning
confidence: 98%
See 1 more Smart Citation
“…Although originally intended for nonlinear programming problems, the augmented Lagrangian method has also been applied to linear programming problems [3,7]. However, neither article assesses its performance on large scale practical LP problems.…”
Section: The Augmented Lagrangian Methodsmentioning
confidence: 99%
“…Thus from (4), (5), and (6), it can be concluded that x * satisfies Karush-Kuhn-Tucker optimality conditions for problem (1).…”
mentioning
confidence: 93%